A mixed-method investigation into international university students’ experience with academic language demands - Russell, Bruce; Barron, Christine; Kim, Hyunah; Jang, Eunice Eunhee (Frontiers in Education, 2022)
Post-secondary education institutions with English as a medium of instruction have prioritized internationalization, and as a result, many universities have been experiencing rapid growth in numbers of international students who speak English as an additional language (EAL). While many EAL students are required to submit language test scores to satisfy university admission criteria, relatively little is known about how EAL students interpret admission criteria in relation to language demands post admission and what their language challenges are. This study, situated at a large Canadian university, integrated student and faculty member focus group data with data obtained from a domain analysis across three programs of study and a reading skills questionnaire. Findings suggest that many students and faculty members tend to misinterpret language test scores required for admission, resulting in surprise and frustration with unexpected level of language demands in their programs. Also, students experience complex and challenging language demands in their program of study, which change over time. Recommendations for increased student awareness of language demands at the pre-admission stage and a more system-wide and discipline-based approach to language support post-admission are discussed.